Metaheuristics and large‐scale optimization - Sakalauskas, Leonidas (Technological and Economic Development of Economy, 2006)
“Metaheuristics and large‐scale optimization” Technological and Economic Development of Economy, 12(1), p. 3. First Published Online: 21 Oct 2010